Causality of Product Awareness Coconut Flour Towards Future Engagement, Indonesian Market - Leonnard Ong; Gabriella Rosellinny; Jonathan Augustinus; Novia Rianti (Sekolah Tinggi Manajemen IPMI, 2018)
In order to establish a future engagement of the Indonesian market in terms of coconut flour, awareness of the product is needed for the consumer decision making to purchase the product which will lead to future engagement. This study aims to examine the effects of product and awareness and consumer decision making towards future engagement in Indonesia. By employing SmartPLS, we prove that existence of product has a relatively strong negative relationship with awareness (.55); while awareness has a relatively weak relationshipwith consumer decision making to purchase a product (.37) and the decision made by customer to purchase healthy product have a relatively strong positive relationship towards engagement of the product in the future (.66). Further implications are discussed.